PENGARUH PENDEKATAN PEMBELAJARAN DAN KOORDINASI MATA TANGAN TERHADAP KETERAMPILAN PUKULAN FOREHAND DRIVE TENIS MEJA PADA SISWA SMK NEGERI 3 KUDUS (Journal of Sport Coaching and Physical Education, 2017)
The purpose of this research is to know about: 1) The difference of influence between massed practice and distributed practice approach to forehand skill of table tennis drive. 2) Differences of forehand skill of a table tennis drive between students who have high hand eye coordination and low eye eye coordination. 3) There is an interaction of the learning approach and hand eye coordination to the forehand skills of a table tennis drive. The design of this research is 2x2 factorial. The sample used in this research is 40 students, which is obtained by purposive random sampling technique. The variables in this study consist of 2 independent variables, namely: 1) manipulative variables consisting of massed practice learning approach and distributed practice learning approach. 2) attributive variable consisting of high and low hand eye coordination. One dependent variable is the forehand skill of a table tennis drive. The techniques and instruments of data collection in this study used tennis ball throw test to measure hand eye coordination.